2017
DOI: 10.1101/222877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic reorganization of nuclear architecture during human cardiogenesis

Abstract: While chromosomal architecture varies among cell types, little is known about how this organization is established or its role in development. We integrated Hi-C, RNA-seq and ATAC-seq during cardiac differentiation from human pluripotent stem cells to generate a comprehensive profile of chromosomal architecture. We identified active and repressive domains that are dynamic during cardiogenesis and recapitulate in vivo cardiomyocytes. During differentiation, heterochromatic regions condense in cis. In contrast, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Consistent with recent reports describing loss of TADs during ESC differentiation 23 , 28 , we also observed that the number of TADs decreased as hESCs differentiated into ventricular cardiomyocytes using multiple TAD-calling algorithms 5 , 10 , 29 ( Supplementary Fig. 4a , b , c ).…”
Section: Resultssupporting
confidence: 91%
“…Consistent with recent reports describing loss of TADs during ESC differentiation 23 , 28 , we also observed that the number of TADs decreased as hESCs differentiated into ventricular cardiomyocytes using multiple TAD-calling algorithms 5 , 10 , 29 ( Supplementary Fig. 4a , b , c ).…”
Section: Resultssupporting
confidence: 91%
“…Their analyses showed that in differentiating hESCs, heterochromatin regions pack more tightly within cis chromosome territories (intra-chromosomal contacts), whereas inter-chromosomal interactions (trans) are likely to occur between active regions localized in the proximity of cardiac-specific genes, such as titin ( TTN ). In general, collective results from RNA-seq, ATAC-seq, and Hi-C revealed that changes in chromatin accessibility occurred concomitantly with changes in RNA expression and large scale genome organization [ 27 ].…”
Section: Applications Of Next Generation Sequencing To Study Heartmentioning
confidence: 99%